The Problem of Economic Development Strategy in Cambodia: The Case of the Road Network - Rasmey, Thach (H. : ĐHQGHN, 2019)
At the upcoming Cambodia national election in July 2018, the Sixth Legislature of the National Assembly will be officially born and also the next national development plan. At present, the five years development plan, called the National Strategic Development Plan 2014- 2018 (NSDP 2014-2018) serves as a roadmap for the government to achieve its policy.